Fabia-Eudokia – żona Herakliusza - Leszka Małgorzata В. (Acta Universitatis Lodziensis. Folia Historica, 2005)
Hereby paper was dedicated to Fabia Eudocia, Emperor Heraclius' first wife. Fabia-Eudocia was the Byzantine Empress for somewhat less than two years. Not much is known about the Empress. However, it is known that she descended from wealthy and influential family from North Africa. As a wife of Heraclius she gave birth to two children: to a daughter Epiphania Eudocia and to a son Heraclius Constantinus. It seems that she may have won the good feeling of subjects’ hearts, most of all of local inhabitants. Her possible popularity may have been to some extent, undoubtedly connected with appreciation for Heraclius at the beginning of his reign. It may have also been the result of sympathy because of her illness, which made it impossible for her to enjoy bringing up children and her position at Heraclius side. Fabia might have also managed to begin some charitable activities, which have always determined an essential aspect of every Empress’ activity and influenced subjects’ attitude towards her. it also seems that liking for deceased Augusta and good remembrance of her were shattered as the society didn’t approve the following Heraclius’ wife, his niece Martina.